Peningkatan Pendapatan Rumah Tangga: Suatu Pengembangan & Pemberdayaan Masyarakat Melalui Konsep Ekonomi Biru di Wilayah Pesisir - Doktoralina, Caturida Meiwanto; Mareta, Sigit; Lestari, Lestari (Jurnal Abdi Masyarakat (JAM), 2024)
Increasing income through the Blue Economy concept in developing and empowering coastal communities is an important concern for the Government of the Republic of Indonesia. Indonesia's vast oceans, with various resources and environmental services in coastal and marine areas, have sufficient potential to achieve a level of self-sufficiency in coastal areas. The government has established 2 (two) strategic policies, the Indonesian Maritime Policy (KKI) and the Blue Economic Development Framework, to manage and sustainably utilize the above environmental resources and services well. For this reason, the urgency of dedication to community development and empowerment in order to increase income in the context of survival has an impact on economic improvement. Through this Community Service Program (PkM), the reviewer will try to provide applicable outputs that can be used by the Government of the Republic of Indonesia in accordance with the downstream concept, especially in the important activities of community development and empowerment in coastal areas. PkM activities apart from this focus on the lack of MSME business actors in Segarajaya Village, Bekasi, West Java in training and knowledge about business management and marketing, for their home business industry. There were 40 participants in the activity. Apart from providing training and empowerment assistance in increasing knowledge for processing activities, this activity will also provide training on household business management using information technology.